2008
DOI: 10.1080/09537100701777303
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for the actin cytoskeleton and cdc42 in regulating platelet integrinα2β1

Abstract: The modified two-site model for platelet activation by collagen requires tight binding of platelets to collagen through integrin alpha2beta1, after its prior activation by inside-out signals initiated by GP VI. The inside-out signalling to alpha2beta1 is not well characterized although it is currently accepted that GPVI initiates signals that lead to regulation of this integrin. The aim of the study was to determine the role played by actin polymerization and the Rho family GTPase cdc42 in the regulation of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…Especially, the up-regulation of collagen type I, IV and V indicated that nickel ions may affect cell structure restoration through promoting the interaction of ECM receptors and generating hypoxia effect in the treated L-929 cells. CDC42, a regulator of cell cycle, can transfer cell signals related to the restoration of actin cytoskeleton and suppress the ROS production in cells [18,19]. In this study, the gene was up-regulated in the treated L-929 cells at 12 h, presuming that it may play a protective action to hypoxic cells and promote the restoration of actin cytoskeleton in the L-929 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Especially, the up-regulation of collagen type I, IV and V indicated that nickel ions may affect cell structure restoration through promoting the interaction of ECM receptors and generating hypoxia effect in the treated L-929 cells. CDC42, a regulator of cell cycle, can transfer cell signals related to the restoration of actin cytoskeleton and suppress the ROS production in cells [18,19]. In this study, the gene was up-regulated in the treated L-929 cells at 12 h, presuming that it may play a protective action to hypoxic cells and promote the restoration of actin cytoskeleton in the L-929 cells.…”
Section: Discussionmentioning
confidence: 68%
“…39 Our results stand in contrast to studies by Pula et al, who found that platelets treated with secramine A show a selective aggregation and adhesion defect in response to collagen. 40 This discrepancy is difficult to explain at present, but it might be related to limited specificity of the inhibitor. The increased secretion in Cdc42 Ϫ/Ϫ platelets stands in clear contrast to observations made in other cell types showing decreased exocytosis upon inhibition of Cdc42, including endothelial cells and mast cells.…”
Section: Discussionmentioning
confidence: 84%
“…Although it is not known whether it is the case with chondrocytes, activation of integrins is regulated by small GTPases in a variety of cells. To date, the involvement of H-Ras, R-Ras, Rap1a, Rap1b, and Cdc42 have been reported (42)(43)(44). Thus, we evaluated the expression of these GTPases in human articular chondrocytes, and found that all of them were expressed at substantial levels ( Figure 5B).…”
Section: ␣V␤5 Integrin Promotes Chondrocyte Dedifferentiationmentioning
confidence: 88%